NoSQL for mere mortals - Sullivan, Dan, 1962- (Hoboken [et all.] : Addison-Wesley, 2015)
"The Mere Mortals tutorials have earned worldwide praise as the clearest, simplest way to master essential database technologies. Now, there's one for today's exciting new NoSQL databases. NoSQL for Mere Mortals guides you through solving real problmes with NoSQL and achieving unprecedented scalability, cost efficiency, flexibility, and availability. Drawing on 20+ years of cutting-edge database experience, Dan Sullivan explains the advantages, use cases, and terminology associated with all four main categories of NoSQL databases: key-value, document, column family, and graph databases. For each, he introduces pragmatic best practices for building high-value applications. Through step-by-step examples, you'll discover how to choose the right database for each task and use it the right way. Whether you're a database developer, data modeler, database user, or student, learning NoSQL can open up immense new opportunities. As thousands of database professionals already know, For Mere Mortals is the fastest, easiest route to mastery"--Back cover.
Part I: Introduction. Chapter 1: Different databases for different requirements -- Chapter 2: Variety of NoSQL databases -- Part II: Key value databases. Chapter 3: Introduction to key-value databases -- Chapter 4: Key-value database terminology -- Chapter 5: Designing for key-value databases -- Part III: Document databases. Chapter 6: Introduction to document databases -- Chapter 7: Document database terminology -- Chapter 8: Designing for document databases -- Part IV: Column family databases. Chapter 9: Introduction to column family databases -- Chapter 10: Column family database terminology -- Chapter 11: Designing for column family databases -- Part IV: Graph databases. Chapter 12: Introduction to graph databases -- Chapter 13: Graph database terminology -- Chapter 14: Designing for graph databases -- Part VI: Choosing a databases for your application. Chapter 15: Guidelines for selecting a database -- Part VII: Appendices. Appendix A: Answers to chapter review questions -- Appendix B: List of NoSQL databases.
Includes index.
Includes bibliographical references (pages 437-439) and index.
Keywords: Non-relational databases